On the Tensile Strength of ABS Produced by Fused Deposition Modelling Process - Kaushik V. Prasad; J. Deepak; H. Adarsha (Current Approaches in Science and Technology Research Vol. 12, 2021)
3D printing is a useful technique in the manufacturing of composites. Parts can be manufactured with high accuracy, low cost, and customizable geometry. Among the various methods, the fused deposition modeling (FDM) is found to be the most versatile method used to produce composites of thermoplastics. This method is highly suitable for producing parts which are complex and have intricate details. The FDM process is gaining popularity owing to the simplicity of the process and minimum tooling required for manufacturing the parts. In the present work we discuss the effect of varying raster angle and layer thickness on the tensile properties of acrylonitrile butadiene styrene (ABS). It is found that as layer thickness increases it reduces the tensile strength also maximum tensile strength is observed in case of specimens having 60o as raster angle.